Alternative protein sources for fish feeds in Egypt - Wassef E.A. (Mediterranean fish nutrition, 2005)
In order to reduce reliance on fishmeal in fish feed formulations, several alternative protein sources or supplements were tested in Egypt. Feeding trials on Nile and blue tilapias, Oreochromis niloticus and O. aureus, gilthead seabream, Sparus aurata, European seabass, Dicentrarchus labrax, and mullet, Mugil cephalus, were conducted. The main target was the efficient utilization of waste animal and plant resources, such as trash fish and macroalgae, for fish feed production. Acid and fermented fish silage, a mixture of fish silage and soybean meal, green and red macroalgae Ulva and Pterocladia meals were all investigated. For each ingredient, a series of experiments were carried out to assess their nutritional properties, amino and fatty acid profiles as well as optimum dietary inclusion level to produce growth performance and feed utilization efficiency equivalent to those of fish meal.
Workshop on Mediterranean Fish Nutrition, 2002/06/01-02, Rhodes (Greece)